Detection of Virulence Genes of Clostridium difficile in Children with Cancer by Multiplex PCR - Hadis Tavafi; Parviz Owlia; Fariba Shirvani; Mozhgan Hashemie; Nader Shahrokhi (Pasteur Institute of Iran, 2014)
Introduction: Toxigenic Clostridium difﬁcile is the major cause of antibiotic-associated diarrhea, colitis, and pseudomembranous colitis. The pathogenicity of C. difficile is related to toxins A&B. Children with cancer are at risk of developing C. difficile infection (CDI) due to increased exposure to antibiotics, immunosuppression, and longer hospital stays. Recently, due to higher sensitivity and speciﬁcity of nucleic acid amplification test (NAATs) compared to toxin enzyme immunoassays (EIAs), many laboratories are transitioning to NAATs for detection of CDI. We aimed to use a multiplex PCR to detect the C. difficile toxin genes tcdA, tcdB and tpi in stool of cancerous children. We also aimed to show the effects of chemotherapy regimens on the prevalence of C. difficile in these children. Methods: 105 fecal samples were collected from cancerous children who were hospitalized and undergoing chemotherapy. The presence of tcdA, tcdB, and tpi genes were tested. Results: C. difficile was identified in 17.14% of children and the detection rate of A-B+ strains was higher than A+B+ and A+B- strains. C. difficile was found in 17.8% of children who received single antibiotic (5/28 cases virulence genes were detected in 4 cases) and in 41.4% of patients who received more than one antibiotics (12/29 cases virulence genes were detected in 8 cases﴿. Conclusion: Multiplex PCR is a powerful technique for preliminary screening and rapid detection of C. difficile and its virulence genes in the stool of cancerous children. The prevalence of C. difficile in cases receiving several antibiotics was higher than those receiving single antibiotics.